2009
DOI: 10.1074/jbc.m109.038034
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Regulates Glucose-stimulated Insulin Secretion through Phosphatidylinositol 4,5-Bisphosphate

Abstract: Membrane cholesterol modulates the ability of glucose to stimulate insulin secretion from pancreatic ␤-cells. The molecular mechanism by which this occurs is not understood. Here, we show that in cultured ␤-cells, cholesterol acts through phosphatidylinositol 4,5-bisphosphate (PIP 2 ) to regulate actin dynamics, plasma membrane potential, and glucose-stimulated insulin secretion. Cholesterol-overloaded ␤-cells exhibited decreased PIP 2 hydrolysis, with diminished glucose-induced actin reorganization, membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 75 publications
(53 reference statements)
2
40
0
Order By: Relevance
“…There is evidence that an increase in the cholesterol content of pancreatic ␤-islet cells decreases insulin secretion. 17 However, given that statin treatment will, if anything, decrease cellular cholesterol levels, this is an unlikely explanation for the observed increase in new-onset diabetes mellitus. It is possible that statins decrease insulin sensitivity in the liver or muscle, although there is no direct experimental evidence to support this.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that an increase in the cholesterol content of pancreatic ␤-islet cells decreases insulin secretion. 17 However, given that statin treatment will, if anything, decrease cellular cholesterol levels, this is an unlikely explanation for the observed increase in new-onset diabetes mellitus. It is possible that statins decrease insulin sensitivity in the liver or muscle, although there is no direct experimental evidence to support this.…”
Section: Discussionmentioning
confidence: 99%
“…Basolateral membrane cholesterol extraction with M-β-CD also reduced the Na + /K + pump activity in A6 renal epithelia [50] . In addition, some reports showed that cholesterol depletion suppressed insulin secretion [51][52][53] , and decreased cholesterol levels in the pancreas may contribute to the severity of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that although antibodies significantly reduced the mobilization of Cy3-actin to the vertex, the population of actin that reached the vertex was able to continue to polymerize in the presence of JP. Many studies have shown that actin polymerization can be regulated by cholesterol and the phosphoinositide PtdIns(4,5)P 2 (Hao and Bogan, 2009;Kwik et al, 2003;Rozelle et al, 2000). However, most of the evidence has been collected at the plasma membrane, and it is unclear whether lipids control actin dynamics on lysosomal organelles.…”
Section: Snares and Hops Regulate Actin Enrichmentmentioning
confidence: 99%